EEGS Findings Among Adults Sudanese Subjects Presented to the National Ribat University - Osman, Makawi A. A.; Taha, Elmutaz H.; Elamin, Eldirdiri M.; Elmagzoub, Mohammed S. (Sudan Journal of Medical Sciences, 2022)
Background: Epilepsy and seizure are one of the most common serious neurological disorders, and most patients either stop having seizures or less commonly die of them. Methods: This retrospective cross-sectional study targeting adult Sudanese patients was conducted in the EEG units of the department of physiology, faculty of medicine, and the National Ribat University. Recordings were obtained from a digital EEG machine (Medtronic pl-EEG). The Statistical Package for Social Sciences (Windows version 15; SPSS) was used for statistical analysis. The study’s main objective was to determine the percentage of abnormal EEGs in adult Sudanese epileptic patients who were referred to the Ribat EEG unit from March 2007 to September 2010. Results: Nine hundred and fifty patients were included in this study, abnormal EEGs was seen in 54.7%, while it was normal was in 45.3%; primary generalized seizures constituted 45.5%, while focal onset seizures were collectively observed in 43.4%, other types of epilepsy counted for 11.2%. Conclusion: This study showed that males were more affected than females, abnormal EEG was maximal in the age group16–30 years. Epileptiform seizure discharges decrease with age, generalized seizure discharges were dominated seizure.